Conceptualising Stakeholder Engagement in Sustainability Reporting - Ardiana, Putu Agus (Jurnal Ilmiah Akuntansi dan Bisnis, 2022)
A plethora of studies reveal that stakeholder engagement is critical in sustainability reporting. However, there is a paucity in the literature on how stakeholder engagement in sustainability reporting may lead to more meaningful sustainability reports. This paper aims to conceptualise the role of stakeholder engagement in producing more meaningful sustainability reports. This conceptual paper offers avenues for future empirical research. This paper contributes to the literature and the theory by shedding light on the importance of institutional work in shifting the institutional logic of stakeholder engagement in sustainability reporting from a strategic management tool to an accountability mechanism so that more meaningful sustainability reports are produced. Stakeholder engagement allows the reporting companies to become more aware of sustainability issues that are informed by their stakeholders while the engaged stakeholders also benefit from the information provided by the reporting companies on the issues, agenda, and performance related to sustainability. Keywords: stakeholder engagement, sustainability reporting, neo-institutional theory